Simultaneous long-lasting regression of multiple nevi and melanoma metastases after ipilimumab therapy. Issue 3 (June 2019) - Plaquevent, Marthe; Greliak, Anna; Pinard, Camille; Duval-Modeste, Anne-Benedicte; Joly, Pascal
Abstract : We report a case of major regression of multiple atypical melanocytic nevi with a vitiligoid reaction in a patient with metastatic melanoma who achieved long-lasting complete remission after ipilimumab therapy. In 2008, a 54-year-old man presented with a dysplastic nevus syndrome. The patient was diagnosed with a scalp ulcerated melanoma (Breslow index 5.1 mm and Clark level IV), which was removed surgically. Four years later in April 2012, the patient was diagnosed with a right parietal skin metastasis, brain, lymph nodes, and bilateral lung metastases. The patient was first treated with vemurafenib, which had to be stopped because of renal toxicity. Disease stabilization was achieved after the second line of treatment with immunotherapy (ipilimumab, four infusions). However, 6 months later, the lung metastases had progressed. The patient was treated with pulmonary stereotactic radiotherapy associated with a second cycle of ipilimumab. After 6 months, he achieved complete remission. Simultaneously, the patient presented a generalized regression of his nevi with a vitiligoid reaction, or halo nevus, associated with a vitiligo located on the hands and inguinal areas. Vitiligo is a frequent immune-related adverse event of immunotherapy. Immunotherapy-induced halo nevus reaction is much less frequent than vitiligo. It was associated in the two case reports from the literature and in our patient with a quick and long-lasting complete remission of nodes and visceral metastases. Therefore, it might correspond to a stronger antimelanocyte immune reaction, associated with a favorable prognosis. The generalized halo nevi reaction in our patient could be more important because of the two cycles of ipilimumab compared with a single one. In conclusion, this case report suggests that a major regression of multiple nevi on ipilimumab might be associated with immunotherapy response.